2015
DOI: 10.1371/journal.pone.0129114
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Annual Additional Effective Doses amongst Minamisoma Children during the Second Year after the Fukushima Daiichi Nuclear Power Plant Disaster

Abstract: An assessment of the external and internal radiation exposure levels, which includes calculation of effective doses from chronic radiation exposure and assessment of long-term radiation-related health risks, has become mandatory for residents living near the nuclear power plant in Fukushima, Japan. Data for all primary and secondary children in Minamisoma who participated in both external and internal screening programs were employed to assess the annual additional effective dose acquired due to the Fukushima … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 18 publications
0
51
1
Order By: Relevance
“…10 We found no significant associations between disease risks and radiation levels post-incident for any of the diseases, which may indicate that the public's understanding of the potential radiation risk had been fostered and public anxiety about radiation exposure might not have been strong enough to influence disease risk. In fact, low-risk dietary and lifestyle behaviours were well examined in our study sites.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…10 We found no significant associations between disease risks and radiation levels post-incident for any of the diseases, which may indicate that the public's understanding of the potential radiation risk had been fostered and public anxiety about radiation exposure might not have been strong enough to influence disease risk. In fact, low-risk dietary and lifestyle behaviours were well examined in our study sites.…”
Section: Discussioncontrasting
confidence: 56%
“…Following Japan's Fukushima Daiichi Nuclear Power Plant incident, triggered by the Great East Japan Earthquake and subsequent tsunami on 11 March 2011, 1 health threats have arisen in the radiationcontaminated areas, and cumulative dose from external and internal radiation exposure is the major public concern. 1-5 Contrary to the concern, as Tsubokura et al and Hayano et al [6][7][8][9][10][11][12][13][14][15] acknowledged in their continuing series of studies and assessments of levels of radiation exposure due to the Fukushima incident, the levels of dose attributed to the incident have been low owing to the weathering process and the success of contaminated food control. The United Nations Scientific Committee on the Effects of Atomic Radiation and the WHO have concluded that the predicted risk of lifetime cancer is very low in the general public, except for the most exposed infants and children in the Fukushima Prefecture, in whom thyroid cancer cases exceeding the norm are estimated by model calculations, although they are difficult to verify in practice due to the low normal rates of thyroid cancer, even a large relative increase represents a small absolute increase in cases.…”
Section: Introductionmentioning
confidence: 99%
“…2, stayed at Iitate for almost 10 h and resided at a place of refuge outside Iitate for 14 hours in each working day; they worked for 5 days and stayed outside of the village for the residual 2 days in each week. Therefore, the annual additional effective radiation dose per year for a person staying full-time in Iitate ( D i ) or staying outside of Iitate full-time (denoted by D 0 ) can be expressed by: right left.5emthickmathspace(3.60.54)=Di×δ+D0×(1δ),δ=10[h]×5[days]24[h]×7[days]0.298. where 0.54 mSv/year is the natural dose in Fukushima Prefecture measured by Chiyoda Technology Corp. [6]. δ corresponds to the fraction of dwell time in Iitate relative to one week.…”
Section: Resultsmentioning
confidence: 99%
“…However, direct measurement of the external exposure at Fukushima was abbreviated [46], and much of the data were estimated from the ambient dose rates determined by airborne monitoring [2, 710]. In general, the summation of the ambient dose rate is much higher than that determined by direct measurements with a semiconducting detector [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation